2023
DOI: 10.3389/fmed.2023.1090168
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous angiosarcoma: A review of current evidence for treatment with checkpoint inhibitors

Abstract: Cutaneous angiosarcoma (cAS) is a rare and aggressive subtype of soft tissue sarcoma with poor prognosis and suboptimal treatment options. Clinical presentation is variable, but cAS often arises from the head and neck. The most widely accepted current approach, surgical excision with adjuvant radiotherapy, is associated with high recurrence rates and can leave patients with profound disfigurement. Chemotherapy and targeted therapy alternatives have had limited success. Thus, there is a significant unmet need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The aforementioned similarity in mutational patterns of head and neck AS to melanomas and the proven efficacy of immune checkpoint inhibition in melanomas and in multiple other cancer types with high tumor mutational burden lay a valuable foundation for future studies ( 25 , 27 , 28 , 33 ). Several smaller studies reported durable responses with checkpoint inhibitors in the treatment of AS ( 34 36 ). An ongoing multi-center Scandinavian phase 2 study is examining this rationale using pembrolizumab combined with the beta-blocker propranolol for advanced AS or undifferentiated pleomorphic sarcoma to study the effect on progression-free survival ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned similarity in mutational patterns of head and neck AS to melanomas and the proven efficacy of immune checkpoint inhibition in melanomas and in multiple other cancer types with high tumor mutational burden lay a valuable foundation for future studies ( 25 , 27 , 28 , 33 ). Several smaller studies reported durable responses with checkpoint inhibitors in the treatment of AS ( 34 36 ). An ongoing multi-center Scandinavian phase 2 study is examining this rationale using pembrolizumab combined with the beta-blocker propranolol for advanced AS or undifferentiated pleomorphic sarcoma to study the effect on progression-free survival ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, propranolol treatment or immunotherapy were proposed for CAS management [ 107 ]. There are also studies showing that patients with angiosarcoma may benefit from anti-PD-1 (programmed death ligand-1) therapy or anti-tumor mutational burden high (TMB-H) [ 107 , 116 , 117 ].…”
Section: Risk Factors Causes and Major Types Of Skin Cancer And Their...mentioning
confidence: 99%
“…Angiosarcomas, which account for 1–2% of all head and neck sarcomas, are extremely rare malignancies that penetrate local structures through anaplastic vascular or lymphatic cells 1 , 2 . Campana et al .…”
mentioning
confidence: 99%